Joseph Black papers - Black, Joseph, 1728-1799.
Volume containing contemporary copies of lectures on chemistry by Professor Black, with the name of John Bacon on the first page.
Professor of chemistry and medicine, Edinburgh, Scotland.
Collection material in English.
Keywords: Bacon, John; Chemistry; Education -- Scotland; Chemists; Educators; Scientists